Factors Associated with Drug Abuse at kipas Foundation Bengkulu City - Rivaldi Rivaldi; Dwi Putri Sulistiya; Suryani Suryani; Sanisahhuri Sanisahhuri; Susilo Wulan (Universitas Islam Negeri Alauddin Makassar, 2020)
Drug abuse is utilization of narcotics which is not for medicinal purposes, but because intention to enjoy its effects, in excessive amounts, more or less regularly, and last long enough, causing physical, mental health and social life. The aims of this study was to determine Factors associated with drug abuse at KIPAS Foundation Bengkulu City. This study uses a qualitative approach with in-depth interview techniques. The informants in this study were 4 main informants from 32 people with age of 12-21 years and 1 counselor informant who knew deeply the problem (key informant). Data analysis technique was done by reducation data, data presentation and conclusion. This study was conducted at KIPAS Foundation Bengkulu City. The results of this study showed from 4 informants said that his personality is quiet, does not care about what happens in their environment and only interact with the same drug users. While the problem of his family often quarreled and some even divorced and were cared less by their parents. Peers influence them by giving drugs for free and they threaten if not use drugs also means not being loyal friends. It is hoped that the Bengkulu City KIPAS Foundation will continue to improve health services for drug addicts by conducting medical therapy, psychosocial therapy, community therapy, religious therapy and also conveyed through posters and leaflets so that residents are no longer involved in drugs.